Ist eine schnelle tiefgehende (und nachhaltige) Änderung in der Vorstellung von Mathematiklehrern möglich? - Reflexion der Erfahrungen eines Fortbildungskurses im Bereich der mathematischen Modellierung - Ambrus, Gabriella; Vancsó, Ödön (Teaching Mathematics and Computer Science, 2015)
Based on the material which was worked out within the project LEMA (2006-2009) pilot-teacher training courses were organized in the six partner countries, so in Hungary as well in the subject: Practice of Modelling tasks in the classroom. According to the tests which were filled out by the participants the conclusion was formulated that they achieved some changes in their pedagogical knowledge and in their estimation concerning their self-efficacy, but they didn't have shown any changes in their beliefs of mathematics and mathematics education. However according to their experience as project partners and leaders of the Hungarian course the authors have the idea that despite of the international results there are changes in this subject in the case of the Hungarian participants. This way can formulated the question:Which changes can be observed in the case of the participants concerning belief towards mathematics and mathematics education after the course and how long-lasting these changes are?The question is examined on the example of two teachers who were participants of the course.